1999
DOI: 10.1046/j.1523-1747.1999.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 15 Expression in Stratified Epithelia: Downregulation in Activated Keratinocytes

Abstract: Keratin 15 (K15) is a type I keratin without a defined type II partner whose expression in epidermal diseases has not been investigated. In this study we have used LHK15, a monoclonal antibody raised against the last 17 amino acids of the K15 polypeptide, to show that K15 is expressed primarily in the basal keratinocytes of stratified tissues, including the fetal epidermis and fetal nail. Although K15 in normal hair follicles was virtually absent from hair bulbs, it was expressed by a subset of keratinocytes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
192
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(211 citation statements)
references
References 58 publications
15
192
0
4
Order By: Relevance
“…The first is an anti-C-terminal peptide polyclonal antibody to K15, IMP15, which enabled double immunofluorescence to be carried out, and the second is a monoclonal antibody, LC18N, which arose fortuitously. These antibodies were used in addition to monoclonal antibody LHK15 (Waseem et al, 1999) to give greater confidence in interpreting immunohistochemistry results. In immunoblots of protein extracted from human epidermis, IMP15 recognizes a band at 50 kDa compared with a 48 kDa band in mouse extracts (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first is an anti-C-terminal peptide polyclonal antibody to K15, IMP15, which enabled double immunofluorescence to be carried out, and the second is a monoclonal antibody, LC18N, which arose fortuitously. These antibodies were used in addition to monoclonal antibody LHK15 (Waseem et al, 1999) to give greater confidence in interpreting immunohistochemistry results. In immunoblots of protein extracted from human epidermis, IMP15 recognizes a band at 50 kDa compared with a 48 kDa band in mouse extracts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…K15 has been reported to be expressed throughout the adult human esophagus based on in situ hybridization (Leube et al, 1988), but more recently it was shown with antibody LHK15 that K15 protein is also confined to the basal layer in human esophagus (Waseem et al, 1999).…”
Section: K15 In Stable Keratinocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Squamous carcinoma cells expressing low levels of K19 were reported to have a higher capacity to invade in vitro, which was decreased by ectopic expression of this IF protein (9). In addition, down-regulation of K15 has been reported in hyperproliferative conditions such as psoriasis and hypertrophic scarring (10), whereas K14 down-regulation was documented in a model of cervical carcinoma (11). However, the relationship between keratin expression and tumor progression remains unclear, as a recent report indicated that K14 overexpression correlated with high-risk squamous cell carcinoma (SCC; ref.…”
Section: Introductionmentioning
confidence: 99%